Biomechanical comparison of implant inclinations and load times with the all-on-4 treatment concept: a three-dimensional finite element analysis. Issue 6 (26th April 2019) - Liu, Ting; Mu, Zhixiang; Yu, Ti; Wang, Chao; Huang, Yuanding
Abstract: The purpose of this study was to compare the effects of implant inclinations and load times on stress distributions in the peri-implant bone based on immediate- and delayed-loading models. Four 3D FEA models with different inclination angle of the posterior implants (0°, 15°, 30°, 45°) were constructed. A static load of 150 N in the multivectoral direction was applied unilaterally to the cantilever region. The stress distributions in the peri-implant bone were evaluated before and after osseointegration. The principal tensile stress (σmax ), mean principal tensile stress (σmax ), principal compressive stress (σmin ) and mean principal compressive stress (σmin ) of the bone and micromotion at the contact interface between the bone and implants were calculated. In all the models, peak principal stresses occurred in the bone surrounding the left tilted implant. The highest σmax and σmin were all observed in the 0° model for both immediate- and delayed-loading models. And the 0° and 15° models showed higher σmax and σmin values. The 0°models showed the largest micromotion. The observed stress distribution was better in the 30° and 45° models than in the 0° and 15° models.